THE ROLE OF SCIENCE AND EDUCATION IN THE DEVELOPMENT OF DIGITAL MARKETING - Adilova Zulfiya Djavdatovna; Bobur Khanturaev Azimovich; Muminova Nargiza Maxsudjonovna (Research Parks Publishers, 2020)
The new global knowledge economy – one powered by information and communication technology (ICT) – is by no means restricted to universities. One understated aspect of the Internet’s impact has been the erosion of universities’ effective monopoly on knowledge creation and curation. With trends in digital marketing getting even more sophisticated, service delivery and marketing analysis are improving throughout industries inclusive of educational institutions. The paper investigates the role of science and education in the digital economy and marketing